Antecedents of e-WOM and Revisit Intention in Sharia Hotels: Application of Social Exchange Theory - Dinisa, Dinda; Gayatri, Gita (Ekonomi Syariah IAIN Kudus, 2023)
Revisit intention is one of the most important factors in determining a hotel’s long-term success, as well as the spread of positive feedback by guests through electronic word-of-mouth (e-WOM). Sharia-compliant hotels, in comparison to conventional ones, face limitations in number and require substantial development. Hence, the primary objective of this study is to examine the factors that influence the creation of eWOM and the intention of guests to revisit, considering the direct, indirect, and moderating influence of guests’ religiosity levels. This study was conducted by distributing questionnaires to 312 respondents, employing the Structural Equation Model- Partial Least Square (PLS-SEM) method for data analysis. The results of this study provide insight into the significant influence of guests’ religious levels in Sharia-compliant hotels on their intention to revisit, directly or indirectly. These findings have significant implications for understanding the essential determinants for attracting returning guests and fostering the more effective growth of Sharia-compliant hotels in Indonesia, contributing to both theoretical insights and practical applications.